PARODY IN PREJUDICED BY AUTHORINFIRES - Farah Malaika Putri; Tri Pramesti (Universitas Negeri Yogyakarta, 2026)
This study discusses the characteristics of parody in Prejudiced by Authorinfires as a fanfiction reinterpretation of classic novel Pride and Prejudice by Jane Austen. Using Linda Hutcheon's theory of parody, this research aims to identify how elements of parody are presented in the text along with critical differences. This study uses a qualitative method with an intrinsic approach, and analyzes the text based on Hutcheon's four main characteristics of parody, namely repetition with critical difference, intertextuality, two-level structure, and critical and interpretive functions. The results show that Prejudiced contains all four characteristics, especially through gender reversal, narrative transformation, and direct quotes from Pride and Prejudice that are reworked. Characters such as Ezra Bennet and Anne Darcy become parodies of the characters in Pride and Prejudice, but with new perspectives that reflect current social issues and power dynamics. Through its dual structure and deliberate ironic distance, Prejudiced functions not only as entertainment, but also as a contextualized and reflective social critique of the classic novel.